Australian Fathers’ Study: What Influences Paternal Engagement With Antenatal Care? - Jeffery, Timothy (J Perinat Educ, 2015)
This mixed-methods study explores factors associated with and levels of engagement of fathers in antenatal care. One hundred expectant fathers were recruited from antenatal clinics and community settings in Western Australia. They completed validated questionnaires. Eighty-three percent of expectant fathers reported a lack of engagement with antenatal care. Factors significantly associated with lack of engagement in multivariate analysis were working more than 40 hours a week and lack of adequate consultation by antenatal care staff. In qualitative analysis, 6 themes emerged in association with a lack of engagement. They were role in decision making, time pressures, the observer effect, lack of knowledge, barriers to attendance, and feeling unprepared or anxious. Care providers should involve fathers in consultations to improve paternal engagement.